2022
DOI: 10.1177/14651165221076444
|View full text |Cite
|
Sign up to set email alerts
|

The impact of EU Cohesion Policy on European identity: A comparative analysis of EU regions

Abstract: This article investigates the role of European Union Cohesion Policy in the development of European identity, drawing on an original and representative survey in 17 regions across 12 member states. We advance a theoretical model which distinguishes cognitive, instrumental and communicative drivers of identity formation. Contrary to existing scholarship, we find that EU Cohesion Policy does contribute to European identity. Citizens that perceive benefits for themselves and for their region's development from EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Still, research has identified ways to promote EU attachment. For instance, Borz et al (2022) found that the EU Cohesion Policy increased the likelihood of developing a strong European identity. Similarly, the introduction of the euro fostered, although to a small extent, European identification (Negri et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Still, research has identified ways to promote EU attachment. For instance, Borz et al (2022) found that the EU Cohesion Policy increased the likelihood of developing a strong European identity. Similarly, the introduction of the euro fostered, although to a small extent, European identification (Negri et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…3 EU identity formation may be influenced by several different factors including cognitive mobilization, instrumental rationality and transnational experiences (see e.g. Borz et al, 2022). Studies suggesting that cognitive mobilization matters for identity formation often emphasise the importance of political skills and ability to process abstract information about distant political entities, such as the EU.…”
Section: Border Proximity and European Identitymentioning
confidence: 99%
“…Audikana et al, 2023;Schraff and Sczepanski, 2022). Instead, studies seeking to understand the individual-level determinants of European identity formation tend to investigate differences in socioeconomic status or attitudes and values, including education, income, ideology, levels of national identification, knowledge about the EU or political interest (Bergbauer, 2018;Borz et al, 2022;Inglehart, 1970). In other words, different segments of the population are seen to respond to various elite attempts to promote a European identity differently, with implications for citizens' responses to the challenges raised by, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the factors contributing to a European identity through participation in the ESC have been both interest-based, in the sense that participants could reap tangible benefits in the form of skills and experience acquisition and thus become Europeanized, and communicative in the sense of being exposed to local cultures, practices and experiences (cf. Borz et al, 2022). The recent calls from the European parliament to supplement the ESC with parallel EU citizenship modules and visits to EU heritage and memory sites in order to ''promote an intercultural and dialogical approach to history and strengthen European values and principles'' (European Parliament, 2022) indicate that 'cognitive mobilization' through greater knowledge acquisition about EU values, citizenship, and the shared history and culture of the EU is also considered an important building block for identity formation.…”
Section: Youth Is Building the European Unionmentioning
confidence: 99%